2020
DOI: 10.1017/s1743923x20000458
|View full text |Cite
|
Sign up to set email alerts
|

The Conditional Effect of Scientific Knowledge and Gender on Support for COVID-19 Government Containment Policies in a Partisan America

Abstract: With the onset of the 2020 COVID-19 pandemic in the United States, many state and local governments were forced to implement necessary policies to contain transmission of the deadly virus. These policies ranged from closing most businesses to more controversial proposals, such as postponing primary elections. In this research note, we examine the role scientific knowledge and gender played in citizen perceptions of these virus containment policies both in the general population and among partisans. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…In response, local and state governments across the United States implemented social distancing measures to control disease contagion (Gupta et al., 2020). However, the willingness to comply with government mandates has varied significantly along partisan lines within the mass public (Algara, Fuller, and Hare, 2020). Much of the existing literature emphasizes that party identification is a potent and powerful force that shapes social distancing behavior and rhetoric (e.g., Grossman et al., 2020; Green et al., 2020).…”
Section: Governmental Social Distancing Recommendations During the Comentioning
confidence: 99%
“…In response, local and state governments across the United States implemented social distancing measures to control disease contagion (Gupta et al., 2020). However, the willingness to comply with government mandates has varied significantly along partisan lines within the mass public (Algara, Fuller, and Hare, 2020). Much of the existing literature emphasizes that party identification is a potent and powerful force that shapes social distancing behavior and rhetoric (e.g., Grossman et al., 2020; Green et al., 2020).…”
Section: Governmental Social Distancing Recommendations During the Comentioning
confidence: 99%
“…Researchers have received different results regarding trust in information sources (Al-Rasheed, 2020;Khosravi, 2020). For example, as to the information provided by scientists on the safety of vaccines, the results of the study show that women show lower confidence (Latkin et al, 2021), while another study found that it was women who had higher confidence in evidence-based information (Algara et al, 2020;Latkin et al, 2021). One more study finds that younger people with higher education have more confidence in evidence-based information, but there is no gender difference (Borgonovi and Pokropek, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Support for and compliance with these policies, evidenced by widespread anti-“lockdown” and anti-mask protests/behaviors and surveys conducted by Pew Research Center [ 5 ], is highly variable, with many heavily in favor and nearly as many heavily opposed. Recent work has attempted to parse out the likely determinants of support and compliance, examining influences such as gender, partisanship, and scientific knowledge and trust [ 6 , 7 ]; race/ethnicity, conspiracy theory beliefs, and COVID-19 knowledge [ 8 ]; and local coronavirus incidence and threat perceptions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%